Pengaruh Penanganan Terhadap Loyalitas Pelanggan dengan Kepuasan Pelanggan sebagai Variabel Mediasi pada PT. Indosat Tbk - Deviana Astika Sari; Ibnu Affan Mahesa Putra; Eksakty Pinastika Ivananta; Atikah Zahra Huwaida; Rahmawati, Rahmawati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The development of telecommunication technology has progressed very rapidly. This advancement has encouraged telecommunication companies, including PT Indosat Tbk, to launch various mobile phone products. Customers will not switch to other products if companies are able to create customer satisfaction, one of which is by handling customer complaints effectively. The purpose of this study is to identify customer performance perceptions, expectations, satisfaction levels, and the aspects that need improvement to enhance complaint handling at PT Indosat Tbk. The results indicate that complaint handling at PT Indosat Tbk has a positive and significant effect on customer satisfaction, with a coefficient of 0.47, as well as on customer loyalty, with a coefficient of 0.36. Customer satisfaction also has a significant effect on loyalty, with a coefficient value of 0.52. Based on the mediation analysis, the obtained value of z = 3.10 with p = 0.002 shows that customer satisfaction significantly mediates the relationship between complaint handling and customer loyalty.